A decade of monitoring micropollutants in urban wet-weather flows: What did we learn?. (1st September 2022) - Mutzner, Lena; Furrer, Viviane; Castebrunet, Hélène; Dittmer, Ulrich; Fuchs, Stephan; Gernjak, Wolfgang; Gromaire, Marie-Christine; Matzinger, Andreas; Mikkelsen, Peter Steen; Selbig, William R.; Vezzaro, Luca
Highlights: Data-driven analysis of micropollutants in 77 wet-weather discharge sites. Top list of micropollutants with high occurrence and risk for surface waters. Combined sewer overflows, stormwater outlets and all chemical classes show risk. Minimum number of required events and sites predicted by concentration variability. Discussion of learnings for future wet-weather flow monitoring. Abstract: Urban wet-weather discharges from combined sewer overflows (CSO) and stormwater outlets (SWO) are a potential pathway for micropollutants (trace contaminants) to surface waters, posing a threat to the environment and possible water reuse applications. Despite large efforts to monitor micropollutants in the last decade, the gained information is still limited and scattered. In a metastudy we performed a data-driven analysis of measurements collected at 77 sites (683 events, 297 detected micropollutants) over the last decade to investigate which micropollutants are most relevant in terms of 1) occurrence and 2) potential risk for the aquatic environment, 3) estimate the minimum number of data to be collected in monitoring studies to reliably obtain concentration estimates, and 4) provide recommendations for future monitoring campaigns. We highlight micropollutants to be prioritized due to their high occurrence and critical concentration levels compared to environmental quality standards. These top-listed micropollutants include contaminants from all chemical classes (pesticides, heavy metals, polycyclic aromatic hydrocarbons, personal care products, pharmaceuticals, and industrial and household chemicals). Analysis of over 30, 000 event mean concentrations shows a large fraction of measurements (> 50%) were below the limit of quantification, stressing the need for reliable, standard monitoring procedures. High variability was observed among events and sites, with differences between micropollutant classes. The number of events required for a reliable estimate of site mean concentrations (error bandwidth of 1 around the "true" value) depends on the individual micropollutant. The median minimum number of events is 7 for CSO (2 to 31, 80%-interquantile) and 6 for SWO (1 to 25 events, 80%-interquantile). Our analysis indicates the minimum number of sites needed to assess global pollution levels and our data collection and analysis can be used to estimate the required number of sites for an urban catchment. Our data-driven analysis demonstrates how future wet-weather monitoring programs will be more effective if the consequences of high variability inherent in urban wet-weather discharges are considered. Graphical abstract: Image, graphical abstract